The Dark and Dry Well: Hidden Psychotic Disorders in Murakami Haruki’s Novel - Zhafira Kania Riveria; Antonius Rahmat Pujo Purnomo (k@ta: A Biannual Publication on the Study of Languange and Literature, 2023)
The personal secrets of humans are just as though a deep and dark well. The peculiarities that occur within human beings not only attract numerous psychiatrists to unravel them but also captivate a Japanese writer, Haruki Murakami. In his novel entitled The Wind-Up Bird Chronicle, he conveys subjective experiences through his main character. The novel tells the story of Toru Okada’s subconscious journey. It is where human memories connect with various ancient subconscious thoughts, strange illusions appear, and unheard voices manifest to ordinary humans. These are common indications of schizophrenia symptoms. The research reveals the challenge in identifying this syndrome, as affected individuals become detached from the “true reality.” Consequently, a more structured approach is deemed necessary to facilitate their reintegration. With the assistance of mythology, wherein this narrative serves as a collectively recognized storyline, those trapped within their fantastical worlds can effectively communicate and establish connections with those residing in the “true reality.